Dominance rank but not body size influences female reproductive success in mountain gorillas - Wright, Edward (PLoS One, 2020)
According to life history theory, natural selection has shaped trade-offs for allocating energy among growth, reproduction and maintenance to maximize individual fitness. In social mammals body size and dominance rank are two key variables believed to influence female reproductive success. However, few studies have examined these variables together, particularly in long-lived species. Previous studies found that female dominance rank correlates with reproductive success in mountain gorillas (Gorilla beringei beringei), which is surprising given they have weak dominance relationships and experience seemingly low levels of feeding competition. It is not currently known whether this relationship is primarily driven by a positive correlation between rank and body size. We used the non-invasive parallel laser method to measure two body size variables (back breadth and body length) of 34 wild adult female mountain gorillas, together with long-term dominance and demography data to investigate the interrelationships among body size, dominance rank and two measures of female reproductive success (inter-birth interval N = 29 and infant mortality N = 64). Using linear mixed models, we found no support for body size to be significantly correlated with dominance rank or female reproductive success. Higher-ranking females had significantly shorter inter-birth intervals than lower-ranking ones, but dominance rank was not significantly correlated with infant mortality. Our results suggest that female dominance rank is primarily determined by factors other than linear body dimensions and that high rank provides benefits even in species with weak dominance relationships and abundant year-round food resources. Future studies should focus on the mechanisms behind heterogeneity in female body size in relation to trade-offs in allocating energy to growth, maintenance and lifetime reproductive success.